Geliat UMKM : Pelatihan dan Pendampingan Penyusunan Laporan Keuangan Berdasarkan PSAK EMKM pada UMKM Laura Pulau Harapan Maninjau - Sri Madona Saleh; Sri Adella Fitri; Nasfizar Guspendri; Mega Rahmi (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2023)
One of Indonesia's sources of economic strength that has endured the epidemic that has been going on since 2020 is MSMEs. MSMEs are a type of industry that can take on labor thanks to labor-intensive business procedures. The UMKM Laura Pulau Harapan is one of the MSMEs found near Lake Maninjau. This MSME works in the food industry and relies on